Health information exposure and obstetric emergency knowledge among pregnant women: a cross-sectional study in Makassar, Indonesia - Alamsyah Alamsyah; Arfinayanti Arfinayanti; Ruqaiyah Ruqaiyah; Samsir Samsir; Tut Handayani; Ayatullah Harun (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Maternal mortality remains a significant public health concern, particularly in low- and middle-income countries where delays in recognizing obstetric danger signs contribute to preventable complications. Adequate maternal knowledge regarding obstetric emergencies is essential for timely care-seeking. This study aimed to examine the association between health information exposure and knowledge of obstetric emergencies among pregnant women attending antenatal care services. Research Methodology: An analytical cross-sectional study was conducted at the Antenatal Care (ANC) clinic of Labuang Baji Hospital, Makassar, Indonesia, from August to September 2025. A total of 45 pregnant women were recruited using accidental sampling. Data were collected using validated questionnaires measuring health information exposure (10 Likert-scale items; Cronbach’s α = 0.856) and obstetric emergency knowledge (20 true–false items; Cronbach’s α = 0.876). Descriptive statistics were used to summarize respondent characteristics. Fisher’s Exact Test and logistic regression analysis were performed to examine associations between variables. Statistical significance was set at α = 0.05. Results: Exposure to maternal health information was significantly associated with knowledge of obstetric emergencies. Pregnant women exposed to health information were nearly seven times more likely to demonstrate good knowledge compared with those who were not exposed (OR = 6.93; 95% CI: 1.18–40.55; p = 0.026). Multivariate logistic regression confirmed that information exposure remained the strongest predictor of obstetric emergency knowledge (OR = 6.96; 95% CI: 1.11–43.41; p = 0.038). Conclusion: Health information exposure plays a critical role in improving pregnant women’s knowledge of obstetric emergencies. Strengthening structured maternal health education within antenatal care services, complemented by community and digital health communication strategies, may enhance maternal awareness and support early recognition of obstetric complications